Effects of Bacterial Melanin on Neuronal Spike Activity in the Rat Sensorimotor Cortex - Petrosyan, T.R.; Gevorgyan, O.V.; Hovsepyan, A.S.; Ter-Markosyan, A.S. (Нейрофизиология, 2015)
We examined post-stimulation changes in the electrical activity of neurons of the rat
sensorimotor cortex after intapraperitoneal injections or direct applications of bacterial
melanin (a strict analog of neuromelanin). Activation of cortical neurons was evoked by highfrequency stimulation of the hindlimb peripheral nerves. The patterns of within-stimulation
responses and long-lasting post-stimulation effects were rather similar in both subgroups
(with systemic introductions or direct applications of melanin). Comparison of the results of
previous electrophysiological experiments, where the effects of melanin on electrical activity
generated by neurons of the substantia nigra pars compacta were studied, showed close
similarities of the effects of this agent (mostly activating influence of bacterial melanin with
the predominance of excitatory/facilitatory post-stimulation modifications of spike activity).
The effects of bacterial melanin can contribute to the recovery processes in neurodegenerative diseases. Ми досліджували постстимуляційні зміни імпульсної активності нейронів сенсомоторної кори щура після внутрішньоочеревинних ін’єкцій або прямих аплікацій бактеріального меланіну (близького аналога нейромеланіну).
Активація кортикальних нейронів викликалася високочастотною стимуляцією периферичних нервів задньої кінцівки. Патерни відповідей у перебігу стимуляції та тривалих постстимуляційних ефектів в обох підгрупах (із
системним уведенням або прямою аплікацією меланіну) виявилися дуже близькими. Порівняння з результатами попередніх електрофізіологічних експериментів, в
яких досліджували впливи меланіну на електричну активність нейронів substantia nigra pars compacta, показало, що спостережувані ефекти (в основному активаційний
вплив бактеріального меланіну з домінуванням збуджувальних/полегшувальних постстимуляційних модифікацій імпульсної активності) були дуже близькими. Ефекти
бактеріального меланіну, ймовірно, можуть бути використані для інтенсифікації процесів відновлення в разі нейродегенеративних захворювань.